2016
DOI: 10.5897/jvmah2015.0380
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of camel brucellosis in three abbatoirs of Nothern Nigeria

Abstract: A sero prevalence study of camel brucellosis was carried out in three abattoirs of Northern Nigeria during the period of October to December, 2013. A total of three hundred and eleven (311) serum samples were collected from Kano, Sokoto and Maiduguri municipal abattoirs. The serum samples were screened using the Rose Bengal plate test with positive samples further tested with the lateral flow immmnoaassay. Out of 180 camel sera collected from Kano Municipal abattoir, 4 (2.2%) were positive for Brucella antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This is in agreement with the findings of Habtamu and Fisseha (2014), who from the Mehoni district in the south-eastern Tigray region of Ethiopia reported a marginally higher significant association with the occurrence of brucellosis in adult camels (>4 years) (6.5%) than in young camels (6 month to 4 years) (0%) with a likelihood odds ratio (OR) of 9.6. Similarly, the current study was in agreement with Madu et al, (2016) who reported 16.7% in adult and 0.6% in young camels with p< 0.05, in three abattoirs from northern Nigeria. Similar to this, the current study found that animals older than 7 years had higher seroprevalence of 7.3% compared to young camels, and this difference was statistically significant (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the findings of Habtamu and Fisseha (2014), who from the Mehoni district in the south-eastern Tigray region of Ethiopia reported a marginally higher significant association with the occurrence of brucellosis in adult camels (>4 years) (6.5%) than in young camels (6 month to 4 years) (0%) with a likelihood odds ratio (OR) of 9.6. Similarly, the current study was in agreement with Madu et al, (2016) who reported 16.7% in adult and 0.6% in young camels with p< 0.05, in three abattoirs from northern Nigeria. Similar to this, the current study found that animals older than 7 years had higher seroprevalence of 7.3% compared to young camels, and this difference was statistically significant (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…A total of 99 research articles spanning 27 states (Plateau, Benue, Kwara, Kogi, Niger, Nasarawa, Borno, Gombe, Yobe, Bauchi, Adamawa, Jigawa, Kano, Kaduna, Katsina, Sokoto, Taraba, Zamfara, Enugu, Anambra, Ebonyi, Edo, Cross River, Akwa-Ibom, Lagos, Ogun, and Oyo states) and the federal capital territory (Abuja) from online database who reported Brucella infection from 1 January 2001 to 31 December 2021 were reviewed. Brucellosis cases were reported in six geo-political zones in Nigeria; in NC [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], NE [ 15 , 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%